The intricate relationship between Unitarianism and the popular sectors, 1820-1829 (Quinto Sol, 2011)
This work analyzes the difficult relationship between the Unitarians and the subaltern sectors between 1820 and 1829. These sectors grew in importance in the novel game of modern politics, and tended to support the interests of their rivals: the Federals. However, we will focus on a less studied topic, looking at how the relationship with Unitarians was established and how it changed over time. Starting from the reforms implemented by Rivadavia, passing on to some of the measures promoted in the Constituent Congress (1824-1827), and finally to certain political practices that identified a way of their own, the negative connotations linked to these practices in which the Unitarians faction operated was successfully exploited by their enemies. As a starting point, we take the hypothesis that an elitist and illustrated view opened a considerable gulf between the Unitarian leadership and the subaltern sectors, which in part –and only in part– was countered at a late stage by charismatic leaders who fought from within the army for the ideas of the centralist faction.
Keywords: rivadavian group; Unitarianism; popular sectors; military leadership; political modernity